The Effect of The Pbb-P2 Incentive Policy on Taxpayer Compliance with Taxpayer Understanding as A Moderating Variable - Taufiq Surya; Haninun (ROE: Research of Economics and Business, 2026)
This study examines the effect of the Rural and Urban Land and Building Tax (PBB-P2) incentive policy on taxpayer compliance, with taxpayer understanding serving as a moderating variable, in Bandar Lampung City. The research adopts a quantitative approach with an explanatory design. Primary data were collected through the distribution of questionnaires to 100 PBB-P2 taxpayers selected using the Slovin sampling technique. The data were analyzed using descriptive statistics, data quality tests, classical assumption tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA). The results reveal that the PBB-P2 incentive policy has a positive and statistically significant effect on taxpayer compliance. Moreover, taxpayer understanding is found to significantly moderate and strengthen the relationship between the incentive policy and taxpayer compliance. These findings suggest that the effectiveness of tax incentive policies is strongly influenced by taxpayers’ understanding of tax regulations and the benefits associated with compliance. Therefore, local governments are encouraged not only to implement incentive schemes but also to intensify tax socialization and educational programs to foster sustainable taxpayer compliance.